Crystal structure and ferroelectric properties of Mn-doped ((Ka0.5Na0.5)0.935Li0.065)NbO3lead-free ceramics - S. Wongsaenmai (2018)
In this study, ceramics in Mn-doped ((Ka0.5Na0.5)0.935Li0.065)NbO3ceramics (Mn content = 0.25, 0.50, 1.00 and 1.50 mol%) were successfully prepared by the conventional mixed-oxide technique. The crystal structure was identified by XRD as a single-phase perovskite structure with tetragonal symmetry. The valence of Mn ions, characterized by the synchrotron XAS technique, was seen to change from Mn4+to Mn3+during the formation of the crystal. The valence state of Mn strongly affected the crystal structure and ferroelectric properties of the ceramics. The ferroelectric parameters show the decrease of remnant polarization and the increase of the coercive field with increasing MnO2content. The results confirm the Mn3+in KNNL perovskite lattices, leading to the formation of oxygen vacancies and hardening effects. © 2011 Elsevier B.V. All rights reserved.